3=-6v+3(v+8)

Simple and best practice solution for 3=-6v+3(v+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=-6v+3(v+8) equation:


Simplifying
3 = -6v + 3(v + 8)

Reorder the terms:
3 = -6v + 3(8 + v)
3 = -6v + (8 * 3 + v * 3)
3 = -6v + (24 + 3v)

Reorder the terms:
3 = 24 + -6v + 3v

Combine like terms: -6v + 3v = -3v
3 = 24 + -3v

Solving
3 = 24 + -3v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '3v' to each side of the equation.
3 + 3v = 24 + -3v + 3v

Combine like terms: -3v + 3v = 0
3 + 3v = 24 + 0
3 + 3v = 24

Add '-3' to each side of the equation.
3 + -3 + 3v = 24 + -3

Combine like terms: 3 + -3 = 0
0 + 3v = 24 + -3
3v = 24 + -3

Combine like terms: 24 + -3 = 21
3v = 21

Divide each side by '3'.
v = 7

Simplifying
v = 7

See similar equations:

| -3(z+2)=24 | | 2n^2+n-36=0 | | x+3x+5=12 | | -2(c-1)=18 | | 4x^2+39x+171=0 | | w+12+2w+2=w+50 | | 2.5x-6=-4-3.5 | | -9x^9y^8(-4x^6z^7+3y^3+3z^8)= | | x^2+y^2-2x-8y-47=0 | | -9x^9y^8(-4x^6z^7+3y^3+3z^8)= | | 15x-48+5x=13x | | (x+4)2+(y+4)2=32 | | xcubed-2xsquared+1=0 | | x-2y=28 | | 6=2-8(1-y) | | (x-5)2+(y-5)2=27 | | xcubed-2quared+1=0 | | 44+q+41=8q+28 | | (x+2)2+y^2=100 | | 2w-5+33=w+48 | | y^2-7y-60=0 | | x^2+(y+2)2=49 | | (x-7)2+y^2=64 | | q+45+45=14q-40 | | x^2+(y-5)2=36 | | 9x-1=7y+8 | | (x-8)2+(y+7)2=225 | | 60h=270 | | 0.9(6x+4)=0.7-(x-3) | | 9x-1=3x+4t | | (x-6)2+(y-1)2=81 | | 15x=840 |

Equations solver categories